Similarities and Differences in the Manifestations of the COVID-19 Epidemic Process in Some Countries - O. P. Chernyavskaya; D. V. Kolodina; T. R. Belova (Эпидемиология и вакцинопрофилактика)
Relevance. The pandemic of a new coronavirus infection has become an unprecedented challenge for modern society. It took the entire population of the Earth by surprise, changing the lives of millions of people in the world in record time. Governments of different countries have reacted differently to the pandemic. The list of preventive measures and the timeliness of their adoption differed. Comparing and evaluating the experience of different countries and emergency response systems will help in the future to use best practices and models to combat future biological threats. The aim of the study was to identify and describe the features of the manifestation of the COVID-19 epidemic process in a number of countries, taking into account the ongoing anti-epidemic and preventive measures, and to hypothesize about the main factors that could potentially influence the differences in the manifestation of the COVID-19 epidemic process. Materials and methods. The choice of countries was conditioned by the purpose to compare the manifestations of epidemic process in our country with the great powers and economies of the world - USA and China and countries (Republic of Belarus and Sweden), which did not introduce lockdown and did not follow all WHO recommendations. To achieve this goal, a descriptive research method was used based on open source data, an analysis of relevant Russian and foreign literature was carried out (scientific electronic libraries PubMed and Elibrary; open sources of statistical information: Yandex DataLens Public: Coronavirus: Dashboard, Johns Hopkins University website, United Nations Population Division, World Bank, Global Panel Database on COVID-19 Pandemic Policy (Oxford COVID-19 Government Response Tracker), as well as the website of the World Health Organization (WHO), Our World in Data, Rospotrebnadzor and some media). Conclusion. The lowest incidence rate is observed in China (on average 315.1 per 100 thousand population [95% CI 314.8–315.4]), and the highest is in the USA (9957.7 per 100 thousand population [95% CI 9954.5–9960.9]). In terms of the number of tests conducted, the United States and Russia are in the lead. To date, the highest vaccination coverage and vaccination rate are observed in the PRC and amount to 92.4% and 90.1%, respectively. In general, these indicators do not reach 95% in all countries, which requires improving the quality of immunoprophylaxis measures. Anti-epidemic measures in the studied countries differed in their set, scope and severity of implementation. In China, Russia and the USA were held in full, and in Belarus and Sweden only partially, some of the events were not held at all. Thanks to the rapid creation of effective vaccines in Russia and China, it was possible to delay the onset of pronounced increases in morbidity at a later date, which, in turn, helped to reduce the burden on the healthcare system. At the same time, despite the obvious relevance of COVID-19, the question of a comprehensive study of the alleged risk factors (biological, social and natural) is still open. There is a certain probability that the virus will now be permanently present in the global population (it will become a seasonal disease).